Tourist Spaces and Tourism Policy in Spain and Portugal - Almeida-García, Fernando; Cortés-Macías, Rafael; Balbuena-Vázquez, Antonia (My University, 2013)
The territorial and geographical factor plays a key role in the development of tourist destinations. The territory and its resources are those that provide identity to the destinations. But tourism resources are not distributed equitably, so that tourism tends to create territorial imbalances. This is explained by the close relationship between tourism and territorial resources (beaches, landscape, heritage, etc.) and the duty to use these resources in the own tourism destination. This study analyses the relationships between tourism, tourism resources and regional imbalances in Spain and Portugal. There are few comparative studies between tourism policy and territorial processes in Spain and Portugal. This is one of the contributions of this study.
Keywords: Política turística; Turismo; Tourist destinations; Tourism Policy